Kebijakan Nonpenal Oleh Kepolisian Resor Batanghari terhadap Tindak Pidana Kekerasan dalam Rumah Tangga di Kabupaten Batanghari - Dedy Syaputra (Wajah Hukum, 2022)
In the case of criminal acts of domestic violence in Batanghari Regency, the Batanghari Resort Police has resolved cases of criminal acts of domestic violence using non-penal channels. However, the obstacle that occurs is that there is no understanding from the people of Batangahri Regency regarding non-penal settlements and the Batanghari Resort Police also does not have a special place for non-penal settlement of cases of domestic violence. The research method used is empirical law so that the research is descriptive, the data sources are primary and secondary sources, the research approach is a case approach, the data collection method is a documentary study and the data analysis in this study is qualitative. The results of the study indicate that the non-penal policy by the Batanghari Police for domestic violence in Batanghari Regency is that non-penal applications have been carried out against perpetrators and newspapers of domestic violence by means of mediation which is directly carried out by the Head of the Women and Children Service Unit as a mediator and obstacle. The obstacle faced by the non-penal policy by the Batanghari Resort Police against domestic violence crimes in Batanghari Regency is the minimum number of personnel in the Women and Children Service Unit and there is no special place for non-penal settlement at the Batanghari Resort Police.